Dewasa dalam Bingkai Otoritas Teks; Sebuah Wacana dalam Mengatasi Perbedaan Penafsiran al-Qur’an - Muh Alwi HS (Institut Agama Islam Negeri (IAIN) Salatiga, 2017)
The difference in the Qur’an interpretation is a big task to be wisely responded, because there are many conflicts, even violence that occurs due to differences and immature attitudes and unwise authority, whereas “a difference does not necessarily end in dispute, and a dispute does not necessarily end in violence.” Therefore, this article tries to analyze and overcome the difference in the Qur’an interpretation. Various factors then become the cause, such as the subjectivity of the interpreter that can not be left behind when reviewing the Qur'an, methods and approaches which are more numerous and different, even the difference of interpretation that can occur caused by the Qur'an itself, for example, it is not clear whether a verse is Muhkam or Mutasyabih, whether a word is special or general, and so forth. Therefore, the difference in interpretation is natural and it becomes a phenomenon commonly found. So that “I may be right, while the other opinion is wrong. On the contrary, it could be my opinion is wrong, and the other opinion is true” is the principle of humility which should take precedence when there is a difference in interpretation, and every result of interpretation should always be ended with a speech Wa Allahu A’lam bi ash-Shawab (God knows most correct).